The Effectiveness of Booklet Local Wisdom Tenun Troso Jepara with Problem Posing Model to Empower Analysis Thinking Skills of Grade VII Students - Istiqomah, Meisya; Suciati*, Suciati; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Universitas Syiah Kuala, 2025)
Booklet of Tenun Troso Jepara applied with problem posing model (PPM) in science learning integrates local wisdom that students are familiar with in everyday life. This research aims to empower students' analysis thinking skills (ATS). In a Junior High School at Sidoharjo District Sragen Regency, this research was conducted. Class VII I as the experimental class and VII D as the control class, with 32 students in each. The sampling technique used was cluster random sampling. A quantitative approach was used in this research with a pretest-posttest control group design. Data were collected through ATS test. Data analysis using quantitative descriptive techniques. The results showed that the experimental group experienced an increase in ATS score by 16.40 points, while the control group by 4.69 points. Based on these results, it can be concluded that the booklet of local wisdom Tenun Troso with the PPM effectively empowers students' ATS